Exploring Carbohydrates for Therapeutics: A Review on Future Directions - Wang, Jie; Zhang, Yukun; Lu, Qi; Xing, Dongming; Zhang, Renshuai (Frontiers in Pharmacology, 2021)
Carbohydrates are important components of foods and essential biomolecules performing various biological functions in living systems. A variety of biological activities besides providing fuel have been explored and reported for carbohydrates. Some carbohydrates have been approved for the treatment of various diseases; however, carbohydrate-containing drugs represent just a small portion of all of the drugs on the market. This review summarizes several potential development directions of carbohydrate-containing therapeutics, with the hope of promoting the application of carbohydrates in drug development.